2015
DOI: 10.3390/rs70201877
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Laser Scanning as an Effective Tool to Retrieve Tree Level Height, Crown Width, and Stem Diameter

Abstract: Accurate measures of forest structural parameters are essential to forest inventory and growth models, managing wildfires, and modeling of carbon cycle. Terrestrial laser scanning (TLS) fills the gap between tree scale manual measurements and large scale airborne LiDAR measurements by providing accurate below crown information through non-destructive methods. This study developed innovative methods to extract individual tree height, diameter at breast height (DBH), and crown width of trees in East Texas. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Principally, a rapid and automated measurement of objects in the three-dimensional space and the creation of dense 3D-point clouds at a millimeter-resolution are possible using terrestrial laser scanning (TLS) [14][15][16][17]. Different algorithms for the automatic detection of individual trees in 3D-point clouds have recently been developed and provide detection rates clearly exceeding 90% [10,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Principally, a rapid and automated measurement of objects in the three-dimensional space and the creation of dense 3D-point clouds at a millimeter-resolution are possible using terrestrial laser scanning (TLS) [14][15][16][17]. Different algorithms for the automatic detection of individual trees in 3D-point clouds have recently been developed and provide detection rates clearly exceeding 90% [10,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Only Hyyppa et al [31,32] evaluated the quality, accuracy, and feasibility of automatic and semi-automatic DBH estimation methods based on high-density TLS data. Moreover, preprocessing conditions (e.g., the thickness of the selected point cloud) also have an influence on the performance of the DBH estimation algorithm (Srinivasan et al [28]), but this has not yet been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Calders et al [20] used a nonlinear least square circle fitting algorithm to estimate DBH to account for potential occlusion in the TLS data. Srinivasan et al [28] removed non-stem points manually before DBH estimation, then the stem point cloud data of three different slice thicknesses were processed by a cylinder fitting algorithm. The resulting diameter of the cylinder was considered as the estimated DBH.…”
Section: Introductionmentioning
confidence: 99%
“…As an active remote sensing technology, TLS can provide a fast and efficient tool for obtaining a dense 3D point cloud dataset containing an immense number of three-dimensional points reflected from scanned objects. Compared with airborne laser scanning and field measurements, TLS can obtain accurate understory information, including a digital record of the three-dimensional structure of forests [3]. Many studies have demonstrated the high potential of TLS in forest inventory, including tree locations [1,[4][5][6], heights [2,3,7], diameters [2,3,6,[8][9][10][11][12][13][14][15], volumes [16][17][18], biomass [17,[19][20][21][22][23] and others forestry parameters [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%